Gender and Stratification - Crompton Rosemary; Mann Michael (Policy Press, 1986)
Major Challenges to pre-existing frameworks of stratification analysis. List of Contributors, Introduction, Class and Status and Gender, Gender and Class and Stratification, A Crisis in Stratification Theory?, Class Analysis and Gender Analysis and the Family, The Relations of Technology, Households and Labor Markets and the Position of Women, Domestic Responsibilities and the Structuring of Employment, Women and the ''Service Class'', Similarities of Life-Style and Occupations of Women, Industrialization and Gender Segregation and Stratification Theory, The Role of Gender in the ''First Industrial Nation'', Gender and Stratification, Notes, Index.